Experimental and Numerical Investigations of a Flexible Rotor on Flexible Bearing Supports - J.-J. Sinou; C. Villa; F. Thouverez (International Journal of Rotating Machinery)
The main goal of this paper is to study, numerically and experimentally, the effects of the bearing support flexibility on the rotor dynamic and the first forward and backward critical speeds. The test rig which is used in this study has been developed and built at the École Centrale de Lyon (France). This flexible rotor, supported by two rolling bearings on flexible supports, is used for three configurations of the flexible supports. The support characteristics are determined experimentally by performing static tests. Moreover, a finite element model of this flexible rotor is presented which consists of a rigid disk on a flexible shaft supported by two bearing supports. On the basis of measured frequency response functions for various rotational speeds, eigenfrequencies and the associated Campbell diagram from the numerical model and the related experimental results for the flexible rotor are discussed. The comparison of these experimental and numerical tests are used in order to update the finite element model and the associated moment stiffness of the two rolling bearings for the three configurations of interest.